Game-Based learning approach to improve students' learning process in a political science subject / Ainatul Fathiyah Abdul Rahim ... [et al.] - Abdul Rahim, Ainatul Fathiyah; Zulkifli, Nursyahida; Mohd Noor, Rafizah; Rahman, Shamsinar; Adnan, Muhammad Ariff Asyrul (UiTM Cawangan Johor, 2018)
Learning politics is vital for students especially in Diploma of Public Administration students. However, they often encounter difficulties in understanding the concepts, theories and processes that lead them to find it very complex, thus, reducing their interest to learn. It has been proven that by using a game-based pedagogical model, it brings benefits in the process to make complex educational concepts more approachable to the learners. Therefore, this paper attempts to explore students' perception towards an education game called "Political Fun Race" game. Political Fun Race is a game that is inspired by one of the popular childhood games - Snakes and Ladders. It is purposely designed to create an exploration to boost the interest of the students in Diploma of Public Administration in seeking political knowledge and it is deliberately developed to help them understand the major concepts in political science such as power, government, law and governance deeper. This game aims to improve the students' learning process via a game as a learning tool to add on besides lectures and traditional classroom. It consists of four (4) divided components (board, dice, counter and questions cards). The questionnaires were distributed to all part two students who enrolled in Course Code PAD120: Political Science in UiTM Raub Campus in order to obtain the information of the study. The results found that majority of the students enjoyed playing this game and agreed that the innovation in teaching really helped them in understanding the subject and it has smoothen the learning process. Besides, it can enhance their general knowledge regarding political science. It is aligned with the aims of the Ministry of Higher Education Blueprint, thus, optimistically it will benefit all students regardless of their course, program, university or country as well as the public.